2017
DOI: 10.1155/2017/9374563
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Ceramide Kinase in Adipogenesis

Abstract: Ceramide kinase (CerK) plays a critical role in the regulation of cell growth and survival and has been implicated in proinflammatory responses. In this work, we demonstrate that CerK regulates adipocyte differentiation, a process associated with obesity, which causes chronic low-grade inflammation. CerK was upregulated during differentiation of 3T3-L1 preadipocytes into mature adipocytes. Noteworthy, knockdown of CerK using specific siRNA to silence the gene encoding this kinase resulted in substantial decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Specifically, the acylation of sphingosine to generate ceramide by CerS has been implicated in many cellular functions, such as cell death, EMT, migration, insulin resistance, and mitophagy, all of which have significant implications in cancer (Hannun and Obeid, 2018). Moreover, ceramide and other sphingolipid species have been shown to directly influence TAG formation (Ordonez et al, 2017). However, the need for pharmacological inhibitors of CerS that are readily usable in animals and humans poses a challenge to a systemic therapeutic approach to the disease.…”
Section: Pharmacological Targeting Of Lipid Acyltransferasesmentioning
confidence: 99%
“…Specifically, the acylation of sphingosine to generate ceramide by CerS has been implicated in many cellular functions, such as cell death, EMT, migration, insulin resistance, and mitophagy, all of which have significant implications in cancer (Hannun and Obeid, 2018). Moreover, ceramide and other sphingolipid species have been shown to directly influence TAG formation (Ordonez et al, 2017). However, the need for pharmacological inhibitors of CerS that are readily usable in animals and humans poses a challenge to a systemic therapeutic approach to the disease.…”
Section: Pharmacological Targeting Of Lipid Acyltransferasesmentioning
confidence: 99%
“…This corroborates the role of ceramide in the pathogenesis of NAFLD with a direct pro-inflammatory effects. In addition, the development of liver dysfunction, hepatic insulin resistance and steatosis in rodents are associated with increased levels of ceramide in both liver and peripheral blood 23. Additionally, adiponectin lowers the hepatic content of ceramide by improving the blood glucose homeostasis through its receptor-associated ceramidase activity 24.…”
Section: Natural History Of Nafldmentioning
confidence: 99%
“…The latter findings could be recapitulated in a different study using 3T3-L1 cells to study preadipocyte differentiation into mature adipocytes. Specifically, it was observed that CERK expression increased during adipogenesis [ 49 ], whereas treatment of the preadipocytes with exogenous C1P inhibited this process [ 50 ]. Likely the effects of C1P may be dependent on different factors such as cellular compartmentalization, the ability of cells to secrete C1P into the extracellular milieu, or the different C1P species that can be produced at a time under specific metabolic conditions.…”
Section: Implication Of Cerk/c1p In Lung Cancermentioning
confidence: 99%
“…Nonetheless, the reader is referred to a recent review by Gomez-Larrauri and co-workers to expand on these aspects [ 46 ]. Lastly, it should be noted that C1P is implicated in inflammatory responses [ 47 , 48 ] and CERK or C1P play key roles in adipogenesis [ 42 , 49 , 50 ]. All of the above cellular functions, namely the upregulation of cell proliferation, survival, and invasion/migration by CerK/C1P, are pro-tumorigenic actions and are hereby discussed in detail.…”
Section: Introductionmentioning
confidence: 99%